Analysis of the odds ratio of developmental delay in children with biliary atresia 12 months after liver transplantation - A. V. Syrkina; O. M. Tsirulnikova; I. E. Pashkova; O. V. Silina; E. V. Chekletsova; S. Yu. Oleshkevich (Вестник трансплантологии и искусственных органов)
Background. Liver cirrhosis occurring before 1 year of age can affect a child’s development. Liver transplantation is the only radical treatment for decompensated cirrhosis. In biliary atresia, cirrhosis develops during the first months of life. The duration of cirrhosis in biliary atresia may vary from palliative Kasai portoenterostomy (PE) to liver transplantation. Developmental abnormalities in children with biliary atresia have been shown to occur both before and after liver transplantation. Association between duration of liver cirrhosis and psychomotor development of children has been underestimated.Objective: to determine the chances of developmental delay in children depending on the cirrhosis persistence duration.Materials and methods. The study enrolled 83 children with biliary atresia (47 children underwent palliative Kasai PE, 36 children with liver transplantation did not undergo Kasai PE). All children had their psychomotor development assessed before PE and 12 months after PE using the Griffiths psychomotor developmental scale (translation and adaptation by E.S. Keshishian) for children up to 24 months of age. Statistical analysis was performed by calculating odds ratios with 95% confidence intervals.Results. Comparative analysis showed that in the subgroup of children who underwent Kasai PE, cirrhosis persistence before transplantation was 2.6 months longer than in children without Kasai PE (p = 0.011). The odds of developmental delay in preparation for liver transplantation were 3.3 times higher in the subgroup of children who underwent Kasai palliative PE compared to children without palliative (95%, CI 1.35–8.31). The odds of developmental delay 12 months after liver transplantation were 4.4 times higher in the subgroup of children who underwent palliative Kasai PE than in children without the palliative care (95% CI 1.54–12.5).Conclusion. Children who underwent liver transplantation after palliative surgical treatment had lower levels of psychomotor development than children without palliative Kasai PE both before and 12 months after liver transplantation (p = 0.0018, p = 0.01 respectively).